La potencialidad cuir en la poesía lesbiana. Un estudio de caso: la Justa Poética, slam de poesía oral - Zani, Alejandra M. (El Colegio de México A.C., 2021)
This paper aims to bring queer theory closer to the contemporary poetry studies and argues for the importance of using some of the tools given to us by this theory within the Latin American context. Our focus is on contemporary lesbian cuir poetry organized by Justa Poética, a poetry slam originated in Buenos Aires. The article was developed through research based on feminist theories and queer theory as a theoretical tool to investigate the construction of subjectivity in poetry, understanding it as a gender technology. The analyzed literature opens up a wide range of possibilities to approach the construction of a lesbian subjectivity in contemporary poetry. This questions the notion that women must become normative females and moves away from gender-based male-female binary categories, and from certain hierarchical discourses about the lesbian body’s normalization.